Perspectives on the biology of uncoupling protein (UCP) homologues. (November 2001) - Adams, S. H.; Pan, G.; Yu, X. X.
Abstract : In mammals, it is believed that a portion of tissue metabolic rate is driven by counteraction of uncoupling, in which the energetically inefficient process of proton leak acts to diminish the mitochondrial electrochemical membrane potential. It is proposed that specific proteins associated with the mitochondrion catalyse uncoupling, and the biology of such putative uncoupling proteins (UCPs) is the subject of active research efforts. UCP4 and UCP5 are interesting in light of their abundant expression in the brain, which may signal an important metabolic function in thermogenesis or regulation of reactive oxygen species in that tissue. While each is expressed to various degrees outside of the brain, their impact on whole-animal metabolism remains to be clarified further. Transgenic mice expressing murine UCP5L, the long isoform of UCP5, using an inducible metallothionine promoter (to drive expression of the transgene in liver, testis, heart, lung, spleen, intestine, kidney and brain) did not display any overt metabolic phenotype, despite liver UCP5L mRNA expression equivalent to that of normal mouse brain. This highlights the need for further studies to examine the nature of UCP5 physiology. Evidence for uncoupling behaviour has recently emerged from studies of the human 2-oxoglutarate carrier (OGC), indicating that the possibility of physiological proton leak elicited by the OGC and other mitochondrial carriers warrants further experimental evaluation.